External Ballistics Simplified Modelof the “RT-400” Rocket Aerial Target - Algimantas FEDARAVIČIUS (Wojskowa Akademia Techniczna, 2018)
“RT-400” rocket aerial target system is described in the paper; research method of its simplified external ballistics characteristics is presented and the obtained results are discussed. This system was designed, tested, and produced by a research team of the Institute of Defence Technologies at Kaunas University of Technology and successfully implemented in practice. One of main aims of this paper was to develop external ballistics’ model of a rocket propelled aerial target which would enable obtaining various ballistic parameters of the investigated vehicle such as its acceleration, velocity, flight angle, flight range and trajectory using as input the internal ballistics data obtained at earlier experimental research of the “RV-12K” rocket motor in a static horizontal test stand for thrust measurements and determination of other internal ballistics’ characteristics such as combustion chamber temperature and pressure. During the experimental research process of the vehicle, under test site conditions, the main aim was to compare accuracy of the obtained external ballistics simulation data with the data obtained during experimental approaches using additional measurement techniques such as radar tracking and crash site and launch site GPS coordinates marking.
Keywords: Balistyka zewnętrzna rakiet